2014
DOI: 10.1039/c4cp02423k
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of ionic and non-ionic surfactants on lysozyme fibrillation

Abstract: Fibril formation is a common property of many proteins, though not all are associated with diseases. Protein surface charges and the added co-solvents play vital roles in determining fibrillation pathways and kinetics. In order to understand these phenomena, the effects of anionic, cationic and non-ionic surfactants on lysozyme fibrillation were studied. Lysozyme forms fibrils in 2 M and 4 M urea solutions following nucleation-dependent and nucleation-independent pathways, respectively, at neutral pH. Under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 59 publications
2
33
0
Order By: Relevance
“…Hence, the radius of gyration (Rg) of human lysozyme was also calculated ( Fig 2b ). Previous experimental studies revealed that at temperatures below the thermal denaturation midpoint (Tm) of lysozyme and in the presence of SDS above its CMC, lysozyme maintained its helicity [ 57 ] but not its β-sheet structure [ 46 ]. As shown in Fig 2b , in the SDS 300 K simulation, the Rg was greater than those of the pure water MD simulations at 300 K and 370 K. This could be due to a number of lysozyme secondary structures, such as β-sheet structures, becoming denatured and thereby causing the lysozyme to lose its native compactness.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the radius of gyration (Rg) of human lysozyme was also calculated ( Fig 2b ). Previous experimental studies revealed that at temperatures below the thermal denaturation midpoint (Tm) of lysozyme and in the presence of SDS above its CMC, lysozyme maintained its helicity [ 57 ] but not its β-sheet structure [ 46 ]. As shown in Fig 2b , in the SDS 300 K simulation, the Rg was greater than those of the pure water MD simulations at 300 K and 370 K. This could be due to a number of lysozyme secondary structures, such as β-sheet structures, becoming denatured and thereby causing the lysozyme to lose its native compactness.…”
Section: Resultsmentioning
confidence: 99%
“…Once partially unfolded, fibril-facilitating conformation is attained, the process becomes downhillpolymerization. In such cases, first-order rate equations can be used to calculate the rate of fibril formation [18,50,51]. This assumption has also been used to investigate the effect of mutations and small ions on the rate of fibrillation.…”
Section: Simple Exponential Kineticsmentioning
confidence: 99%
“…Urea has a weaker denaturing effect, and does not reach a maximum nucleation rate until the concentration is above 6 M. We note that the two orders of magnitude enhancement between 2 M and 4 M urea (Figure 4) is qualitatively consistent with the observation that the lag time for lysozyme aggregation disappears over this range. [43]…”
Section: The Effect Of the Folded State On Nucleationmentioning
confidence: 99%